Alternatif Penyelesaian Sengketa Lelang Lebak, Lebung dan Sungai di Kabupaten Ogan Ilir - Indrajaya Indrajaya (Wajah Hukum, 2022)
For a long time, people in several sub-districts of Ogan Ilir Regency who live on the banks of the river have used flooded areas or puddles of water around the river due to river overflow to become one of the sources of PAD in the field of fisheries. Utilization is carried out by conducting auctions in lebak, lebung and rivers which are regulated in the Regent's Regulation on the management of fishery resources. In addition to being the legal basis, this regional regulation also aims to protect the environment in the Lebak, Lebung and river areas from damage caused by fishing by the Manager (the winner of the auction). Managers who do not carry out the management of lebak, lebung and rivers according to the rules may be subject to criminal sanctions or fines. This study aims to find out how the dispute resolution of the lebak lebung auction between the parties in practice is carried out. The problem in this study is how the forms of dispute resolution in the Lebak Lebung auction are carried out by the parties in practice. This type of research is normative legal research using a statutory approach. From the results of the study, it can be concluded that the settlement of disputes between the management committee and the management of lebak lebung and rivers is in practice mostly resolved by deliberation mediated by the village head or local village head, but if no agreement is found then the settlement is through the courts.